Modelling and control of the doubly-fed induction generator - He, Zhengbo. (2014)
Currently, mankind is faced with two pressing issues about energy and environment, therefore the use of renewable, green energy-wind energy, hydropower and solar energy as an important clean alternative energy is extensively spread which has a great significant effect over the world in recent years. Among these renewable energies, the unique advantages of wind energy draw much attention from scholars of various countries. Wind power technology has become a hot research topic. And the research about the control of wind power systems has become a hot topic. In this regard, people in the world are devoted to develop the technical innovation. Among all these technologies, wind power system of variable speed fixed frequency is most widely used, especially in the use of wound asynchronous motor as doubly-fed machine. Based on this system, the back-to-back AC frequency converter is controlled by the control system to realize the utilization of maximum wind power in the wind energy conversion system with doubly-fed induction generator.